PHYTOCHEMICAL EVALUATION OF ANTI-INFLAMMATORY AGENTS OF STARFRUIT LEAF EXTRACT (Averrhoa bilimbi) FROM URBAN AREA - Tahara Dilla Santi; Aditya Candra; Ika Waraztuty; Andri; Said Aandy Saida; Syarifah Nora Andriaty (PT. Radja Intercontinental Publishing, 2025)
Inflammation is the body's natural defense mechanism against infection or injury.This study aims to evaluate the phytochemical compounds contained as anti-inflammatory agents in starfruit leaves grown in urban areas. The methods used in the study include laboratory tests to obtain soil characteristics including physical and chemical properties, phytochemical screening tests and GC-MS to obtain accurate data related to the bioactive compounds contained in starfruit leaves. The results showed that starfruit leaves contain alkaloids, steroids, saponins, flavonoids, phenolics, and terpenoids, but no tannins were found. This may be due to the clay soil structure where the plant grows which affects the secondary metabolites produced. Furthermore, the GC-MS test obtained thirteen compounds which are anti-inflammatory agents including 2-(p-tolymethyl)-p-xylene; cis-tricyclo [7.5.0.0(2,8)]tetradeca-7,9-diene; (2E,6E,10E)-3,7,11,15-tetramethylhexadeca-2,6,10,14-tetraen-1-ol; (2E,7R,11R)-3,7,11,15-tetramethyl-2-hexadecen-1-ol; Dimethyl (3S,4R,5S,6R)-3,6-dimethylcyclohexene-4,5-dicarboxylate; 9,12,15-Octadecatrienol; Palmitic acid; 2-amino-4,4,6,6-tetramethyl-4,6-dihydrothieno[2,3-c]furan-3-carbonitrile; 2(3H)-Phenanthrenone, 4,4a-dihydro-4a-methyl-; 4,8-Dimethyl-3,7-nonadien-2-ol; Benzofuran, 2,3-dihydro-; Acrylic acid; 4-Hydroxy-3-methyl-2H-pyran-2-one.